COLONIAL POLITICS IN FORMING ETHNIC IDENTITY OF MELAYU MINANGKABAU AND BATAK IN TAPANULI - Ida Liana Tanjung; Bambang Purwanto; Nur Aini Setyawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
The article discusses the forming of ethnic identity among Batak and Malay people in Tapanuli during colonial period. The colonial government that desired to expand its hegemony among these ethnic groups had led them to create policies and boundaries for the groups in Tapanuli. This study uses historical method (heuristic) that begins from sources collection, sources critique,interpretation and explanation. Constructive approach is used to analyze the sources that considers ethnic identity is a result of construction process of a particular group. This article shows that in pre-colonial period it was difficult to determine ethnical boundaries in Tapanuli, particularly the Malay, Minangkabau, and Batak. However, after the Dutch government expanded its expansion to this region, the ethnical boundaries began to form and the differences among them became apparent. Ethnic segregation policy implemented by the Dutch and its support to the Batak ethnic group and the Christian obviously had formed and changed the awareness of ethnic identity among Batak and Malay people. In the early 20th century, the colonial government featured and strengthened the ethnic identity awareness in Batak community.